2018
DOI: 10.12809/hkmj176823
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial valve for treatment of persistent air leak complicating spontaneous pneumothorax

Abstract: Only a small proportion of cases of endobronchial valve implantation for air leak complicating pneumothorax had unequivocal success. Intact bilateral interlobar fissures appear to be a necessary, though not sufficient, condition for success. Patients with fewer medical co-morbidities and immediate air-leak cessation after endobronchial valve implantation have a higher likelihood of success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The median time from chest tube to bronchoscopy was 25 days. The location of the air leak could not be identified in 17 (46%) patients and of the remaining 20, only 8 (40%) were successful in stopping the air leak and allowing the chest drain to be removed [ 44 ]. A retrospective study in the US reported success in 48/60 (80%) patients who received EBVs for PAL in the context of SP or iatrogenic pneumothorax [ 45 ].…”
Section: Overview Of Management Of Secondary Spontaneous Pneumothoraxmentioning
confidence: 99%
“…The median time from chest tube to bronchoscopy was 25 days. The location of the air leak could not be identified in 17 (46%) patients and of the remaining 20, only 8 (40%) were successful in stopping the air leak and allowing the chest drain to be removed [ 44 ]. A retrospective study in the US reported success in 48/60 (80%) patients who received EBVs for PAL in the context of SP or iatrogenic pneumothorax [ 45 ].…”
Section: Overview Of Management Of Secondary Spontaneous Pneumothoraxmentioning
confidence: 99%
“…EBV success requires evaluation for fissure completeness and collateral ventilation, quantification of air leak, and precise localization of the leak site; all have shown to have an impact on a successful outcome [10][11][12][13][14]. Failures are common, and the overall success rate was reported to be 22% in spontaneous PTX [15]. Detailed discussion about the patient selection, management and follow-up is a broad topic and beyond the scope of our study.…”
Section: Discussionmentioning
confidence: 98%
“…An interesting finding is that a higher comorbidity burden appears to be a risk factor for delayed recovery, regardless of the EBVs implantation status. 59 To reduce the risk of infection, migration and granulation tissue formation, it is now recommended that the valve be removed 4–6 weeks after placement or upon resolution of the air leak. 60 Furthermore, the cost of these valves is a drawback that prevents their widespread use in clinical practice.…”
Section: Introductionmentioning
confidence: 99%